The problems and challenges in the implementation of compulsory attendance order in Malaysia - Fauziah Hani binti Ahmad Fuzi (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2019)
This research analyses the problems and challenges in the implementation of Offenders Compulsory Attendance Order (“the Order”) under the Offenders Compulsory Attendance Act 1954 (“the Act”) in Malaysia. In doing so, the researcher discusses the reasons on why the Act was forgotten after the year of 1972 and was only revived about three decades later i.e. in 2010. The disappearance for a very significant period begs the question as to its efficiency, the problems, limitations, and shortfall in the application of the Act. This research also discusses the problems and challenges in the implementation of the Order after its revival in 2010. The question that follows is whether it will continue to be used alongside other non-custodial sentences available in the current Malaysian penal system. Since the Order is strikingly similar to the application of suspended sentence in other jurisdictions for example the United Kingdom and Australia, therefore this research explores about the application of suspended sentence in those countries so that Malaysia can learn from their experience on how this kind of Order can be implemented successfully. For the purpose of this qualitative research, data and information are collected from the libraries and internet resources. However, due to scarcity of academic literatures on the topic especially pertaining to the application of the Order, the researcher opts to conduct interviews and online survey among the Compulsory Attendance Offenders, Prison Officers, and Magistrates to gather the first-hand data and information. Comparative study is also used in order to discuss and determine how the Order differs from other forms of non-custodial sentences as provided in the Criminal Procedure Code such as Community Service Order and Bond of Good Behaviour Order. This research finds that the Order is not only able to achieve the goal of sentencing but it is indeed cost-effective, sustainable, and correlation in reducing the prison congestion problem. However, since the Act itself contains lacunae and weaknesses, it makes the efficacy of its implementation easier said than done. Therefore, this research is concluded with recommendations such as to make amended to the Act to ensure that the imposition of the Order will benefit not only the offenders, but also the government and the society.